Gender beliefs and norms underlying intimate partner violence stigma among women living in Botswana: Results of an exploratory factor analysis. - Ari Ho-Foster; Mercilene Tanyaradzwa Machisa; Lorato Ruth Moalusi; Nicola Christofides (PLOS Global Public Health)
Gender inequitable beliefs, blaming attitudes, externalised and internalised stigma are commonly recognised barriers for intimate partner violence (IPV) survivors seeking help. However, the measurement of IPV stigma, its associations with inequitable gender beliefs and impacts on survivor disclosure, help-seeking behaviours, and mental health outcomes remain understudied. We explored women's agreement with statements about gendered power dynamics and violence in intimate heterosexual relationships, before identifying and psychometrically testing scales derived for measuring community norms and beliefs underlying stigma to IPV. We used data from a nationally representative sample of 596 women living in Botswana. Exploratory factor analysis (EFA) occurred with responses of IPV survivors, and involved items from the Community Ideas about Gender Relations, Community Ideas about Rape, and Gender Equitable Women Scales. For each EFA identified scale, we estimated reliability (McDonald's omega (ω)) and correlation with psychosocial outcomes related to IPV stigma. Among IPV survivors, we also considered whether survivors had disclosed their experience of abuse to others prior to the interview. Some 40.9% (n = 244) of women have experienced physical and/or sexual IPV at least once in their lives. Among them, an EFA of 31 gender beliefs and norms identified three latent variables: community norms about male dominance over female partners (C-MDP) (11 items; ω = 0.86); respondent beliefs about male dominance over female partners (I-MDP) (12 items; ω = 0.83); and survivor blaming attitudes (SBA) for the IPV they experienced (8-items; ω = 0.83). Some 15% of survivors had attempted suicide in the past, 8% had disclosed having suicidal thoughts, 49% were considered at risk for depression, and 18% at risk for post-traumatic stress disorder. Survivors who more strongly endorsed C-MDP appeared more likely to have attempted suicide (p = 0.04), and less likely to have disclosed their IPV experience prior to the study (p = 0.002). Survivors who more strongly endorsed SBA appeared more likely to have had suicidal thoughts (p = 0.02) and greater post-traumatic stress symptoms (p = 0.06). C-MDP, I-MDP and SBA appear related to psychosocial and disclosure outcomes. Gendered social norms may play an important role in understanding how survivors experience IPV stigma. We recommend further research into culture-informed practices that act to socialise such norms.